Single Particle Momentum Distributions for Three-Bosons in Two and Three Dimensions and Dimensional Crossover - Bellotti, F. F.; Yamashita, M. T. [UNESP] (Springer Nature, 2015)
In this paper, we review our main results involving the single particle momentum distribution of bosonic trimer states in two and three dimensions. A summary table makes easier the comparison between the matrix elements and the different terms of the momentum distributions. We also show a practical method to continuously interpolate between different dimensions.